1999
DOI: 10.1111/j.1572-0241.1999.01086.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Hemodynamic Changes in Mansonic Schistosomiasis With Portal Hypertension Treated by Azygoportal Disconnection and Splenectomy

Abstract: The data allowed us to conclude that hepatosplenic schistosomiasis induces a hyperdynamic circulatory state that was corrected after splenectomy and azygoportal disconnection, remaining a mild pulmonary hypertension. Therefore, these changes are correlated with the portosystemic collateral circulation, especially as a consequence of splanchnic hyperflow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Based on well-established findings [10,11,28,41,51], increased hepatic arterial flow with reduced portal blood flow cannot be justified, as is well documented in HSS, by portal overflow. It can be suggested that the total hepatic flow in HSS is actually increased by increasing flows in both vascular beds.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Based on well-established findings [10,11,28,41,51], increased hepatic arterial flow with reduced portal blood flow cannot be justified, as is well documented in HSS, by portal overflow. It can be suggested that the total hepatic flow in HSS is actually increased by increasing flows in both vascular beds.…”
Section: Discussionmentioning
confidence: 96%
“…Some angiographic studies have reported small participation of the arterial sector in the hemodynamics of HSS, demonstrating reduction in hepatic artery diameter and poor intrahepatic arterial vasculature [9][10][11]43]. Those authors suggested that, as a result of massive splenomegaly, the splenic artery hypertrophy would deviate the hepatic artery flow.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reported incidence of PVT in patients with HSS is 33% [6]. A high incidence ranging from 17-63% is observed in patients undergoing splenectomy [5][6][7][8] with a 6.12-fold higher risk in these patients [6]. PVT can further accentuate portal hypertension with complications, such as GI bleeding due to varices, ascites, portal biliopathy, and portosystemic encephalopathy [9] Moreover, it is associated with a hepatic carcinogenic potential since reduced hepatic blood supply causes parenchymal changes [10].…”
Section: Introductionmentioning
confidence: 99%